Utilização de algas como bioindicadoras de toxicidade em ambiente aquático semi natural - Fagundes, Márcia Regina da Silva (1997)
Experiments were carried out on microcosms to measure the toxicity of both cassava industrialisation residue and gelatin industry residue. Physicchemical and biological parameters were analysed by using as toxicity bioindicator an algae community from a semi-natural aquatic environment. This semi-natural environment was obtained by addition of effluents to natural water coming from Horto Florestal de Maringá. Natural water, without addition of effluent, was also used as a control microcosm. During a period of 60 days, samples were taken from each microcosm. Physic-chemical and biological analyses were performed in these samples on 3rd, 7th, 14th and 25th days and after the 25th day in intervals of 5 days. Parameters such as pH, conductivity, COD, DO, trace elements (iron, calcium, zinc and chrome), nitrate, nitrite, ortho-phosphate, total dissolved phosphorus, chlorophyll a were analysed. Results demonstrate that the residue from cassava industrialisation was the one which caused mayor effects on the algae community growth. The addition of cassava residue shows that the greater concentration values of chlorophyll a for phytoplankton and periphyton, occurred on 35th Day with 200μg/L e 2,7μg/cm2 , respectively. In the microcosms, which received gelatin residue the greater chlorophyll a concentration value for phytoplankton occurred on the 30th day (9,0μg/L) while for periphyton occurred 45th day (0.6μg/cm2). Results shows an increase in the algae biomass. This increase can be related to the addition of nutrients, specially nitrogen and phosphorus, which are present in cassava residue. In a general form, was observed that there was a difference among dominant genders according to the type of effluent used. In microcosms with cassava residue was observed to be the Chroococcus (Cyanophyceae), in both phytoplankton and periphyton, the dominant gender. On the other hand in microcosms with gelation residue the dominant genders were Stigeoclonium (Chlorophyceae) e Nitzschia (Bacillariophyceae) for phytoplanktonics and periphytics communities, respectively. Cryptomonas (Cryptophyceae) was the dominant gender observed in the natural water, which was used as control microcosm. The results from this work infer that the used methodology has a great potential for monitoring lakes and possibly rivers.